PROCEEDINGS OF DIVORCE FOR WOMEN ACCORDING TO FIQH AL-SHAFI'IYYAH AND POSITIVE LAW - Nurdin (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Divorce Delegation for Women According to Fiqh Al-Syafi’iyyah and Positive Law